Spinon confinement and a sharp longitudinal mode in Yb2Pt2Pb in magnetic fields - W. J. Gannon (Nature Portfolio, 2019)
The behavior of quantum magnets depends strongly on the effective dimensionality of the inter-spin interactions. Here the authors tune the influence of two- and three-dimensional couplings in Yb2Pt2Pb with a magnetic field and hence control the behavior of emergent one-dimensional excitations.